Integrating online community support into outpatient breast cancer care: Mayo Clinic Connect online platform. (October 2021) - Harmon, David M; Young, Colleen D; Bear, Melissa A; Aase, Lee A; Pruthi, Sandhya
Introduction: Mayo Clinic Connect is an online community of over 100, 000 members who support each other through sharing lived experience when facing and managing new diagnoses. The community is moderated by Mayo Clinic staff and volunteer patient mentors. Methods: Mayo Clinic breast clinic patients undergoing evaluation received a binder of support resources including a brochure about Mayo Clinic Connect at visits between January and May of 2019. Surveys were distributed at subsequent visits between May and December of 2019 to assess patient awareness about the online resource, participation frequency, purpose of use, and benefits for members, as well as reasons for not joining (non-members). The primary aim was to assess patient resilience, coping, and self-management after joining the online community. Results: Nine hundred surveys were distributed, and 102 participants completed surveys between May and December 2019. Forty-five percent ( n = 46) had heard about Mayo Clinic Connect; 34% ( n = 15) through a brochure. The remainder heard about the community from a Mayo Clinic provider (43%; n = 19) or other resources (22%, n = 10; no response n = 2). Twenty percent ( n = 20) of survey participants registered as Breast Cancer group members, and most of this subgroup (55%; n = 11) reported understanding diagnosis, treatment plans, and finding peer support as reasons for joining. Seventy-five percent of Mayo Clinic Connect participants ( n = 15) reported the community met or exceeded expectations. Conclusion: This pilot study reveals the potential positive impact of introducing an online peer support group into clinical care plans for patients coping with a new and anxiety-provoking cancer diagnosis.